GIG ECONOMY: What is the Impact on Top Talent Recruitment and Labour Skill Market for Freelance Workers in the Millennial Generation in DKI Jakarta? - Hasan, Diana; Nuraeni, Nuraeni; Nursyirwan, Vivi Iswanti; Tantri, Mitsalina; Kinasih, Dini Hadiati Putri (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
The aim of this research is to measure freelance workers' perceptions of the impact of being part of the Gig Economy. This research also aims to find out the perceptions of workers, especially the millennial generation, from various types of freelance work through the Gig Economy, Top Talent Recruitment and Labour Skill Market variables from working in the gig economy sector. This research uses descriptive analysis of respondents with purposive sampling data collection techniques, namely the sample in this study was selected based on the characteristics and objectives of respondents regarding the opportunities and challenges of working freelance as part of the gig economy. Quantitative research method with the data source for this research is the primary data source obtained from distributing questionnaires directly to respondents as well as secondary data, namely from observing documents and research that supports this research. Questionnaires were distributed using a purposive sampling technique to the population of millennial generation freelance workers in the DKI Jakarta area, to determine the research object. The data collection technique used is by distributing questionnaires or questionnaires. The data statistical methods used are descriptive statistics and Partial Least Square (PLS) with the SmartPLS version 3.0 program. The results of this research are that Recruitment Top Talent influences the Labour Skill Market, the Gig Economy is estimated to influence the Labour Skill Market, and the Gig Economy influences Recruitment Top Talent.